Implementasi P5 dalam Kurikulum Merdeka di MA Matholi'ul Anwar Simo Sungelebak Karanggeneng Lamongan (AJER: Advanced Journal of Education and Religion, 2025)
This study investigates the implementation of the Pancasila Student Profile Reinforcement Project within the Merdeka Curriculum at MA Matholi'ul Anwar Simo Sungelebak Karanggeneng Lamongan. The background of this research is rooted in the national educational objectives to develop students who are not only academically proficient but also possess strong moral and character foundations aligned with Pancasila values. The study employs a qualitative descriptive approach, specifically a case study method. Data was collected through passive observation, semi-structured interviews with key informants, and relevant document analysis. The research revealed that the Merdeka Curriculum, implemented since the 2022/2023 academic year, has been integrated into all classes and subjects at MA Matholi'ul Anwar. However, some classes have not fully adopted the curriculum. The findings indicate that the Pancasila Student Profile is effectively utilized to reinforce character education, emphasizing the development of critical thinking, creativity, and innovation among students. The project implementation in class X adhered closely to the guidelines provided in the Pancasila Student Profile Development Project Handbook, covering the planning, execution, and evaluation stages. Significant improvements were observed in key dimensions such as religious devotion, global diversity, cooperation, and creativity. This study concludes that the Merdeka Curriculum and the Pancasila Student Profile Project have shown positive results in character development at MA Matholi'ul Anwar, reflecting the curriculum’s potential to foster holistic student growth in line with national educational goals.